Long‐term quality of life after liver transplantation for non‐resectable colorectal metastases confined to the liver. Issue 2 (25th October 2018) - Dueland, S.; Line, P.‐D.; Hagness, M.; Foss, A.; Andersen, M. H.
Abstract : Background: Liver transplantation for patients with non‐resectable colorectal liver metastases offers increased survival, with median overall survival of more than 5 years. The aim of this study was to compare quality of life before and up to 3 years after liver transplantation for colorectal liver metastases. Methods: Quality of life was assessed using the European Organisation for Research and Treatment of Cancer QLQ‐C30 questionnaire version 3.0. The patients received the questionnaire before and up to 3 years after liver transplantation. Results: Some 23 patients were included in the analysis. Three months after liver transplantation they reported reduced quality of life (global health status scale), physical function and role function, and increased dyspnoea. At 6 months, global health status, physical function and role function had returned to pretransplant values. Three years after liver transplantation all symptom and function scores were comparable to baseline values. Patients with high scores for fatigue, pain and appetite loss at baseline had reduced 3‐year overall survival. Conclusion: Patients with non‐resectable colorectal liver‐only metastases receiving liver transplantation had good long‐term quality of life. Patients with high symptom scores before transplantation had reduced 3‐year overall survival. Abstract : Patients with non‐resectable liver‐only metastases receiving liver transplantation had good long‐term quality of life with values comparable to baseline levels. Patients with high symptom scores before transplantation had reduced 3‐year overall survival. Good QOL in highly selected patients